2018
DOI: 10.4314/jfas.v9i5s.6
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism to assess the relationship between socio-technical congruence and project performance in incremental model

Abstract: Socio-technical congruence (STC) is one of the emergingPrior study on STC suggests that the congruence between socio and technical dependencies leads to increase in task performance. However, little is discovered on how it relate to task performance in software development paper, we outline a method to investigate the relationship of STC and task performance in Journal of Fundamental and Applied Sciences

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The system's resilience was assessed using simulation-based methods, whereas the system managers were considered decision-makers. Similarly, Sobri et al [105] presented a novel method to determine the relationship between STC and team performance using an incremental software development model.…”
Section: ) Cluster 4: Socio-technical Congruencementioning
confidence: 99%
“…The system's resilience was assessed using simulation-based methods, whereas the system managers were considered decision-makers. Similarly, Sobri et al [105] presented a novel method to determine the relationship between STC and team performance using an incremental software development model.…”
Section: ) Cluster 4: Socio-technical Congruencementioning
confidence: 99%
“…To analyze the evolution in STC domain, the keywords and keyword plus were extracted from the selected pool of studies (Datta, 2018;Cataldo et al, 2013;Portillo, 2013;Sarma et al, 2008;Colfer et al, 2016;Wang et al, 2018;Portillo-Rodríguez et al, 2014;Kwan et al, 2009;Šmite et al, 2017;Ehrlich et al, 2008;Bolici et al, 2009;Šmite et al, 2012;Jiang et al, 2012;Gokpinar et al, 2010;Valetto et al, 2008;Zhang et al, 2012;Bernardi et al, 2012;Betz et al, 2013;Marczak et al, 2009;Cataldo et al, 2009;Sobri et al, 2017;Calefato & Herbsleb, 2017;Bird et al, 2011;McLeod L, MacDonell et al, 2011;Kiani et al, 2013;Nguyen et al, 2008;Wagstrom et al, 2010;Avnet, 2016;Bettenburg, 2011;De Santana et al, 2013;Suali et al, 2017;Syeed et al, 2013;Golzadeh, 2019;Palyart et al, 2017;Zhang et al, 2019;Tamburri et al, 2019) for the period from 2008 to 2019. Furthermore, keywords facilitate the collection of additional information by considering various aspects like the research article, journal name, year of publication, and research field.…”
Section: Rq2 How Did Stc Evolve Over the Time Period From 2008 To 2019?mentioning
confidence: 99%
“…Furthermore, Sobri et al (2017) examined the impact of STC on an incremental model by analyzing the resolution time (time to resolve a bug) in software development. By applying linear regression analysis, the results indicated that congruence (among communication logs and file changed together) has significant effects on task performance.…”
Section: Rq2 How Did Stc Evolve Over the Time Period From 2008 To 2019?mentioning
confidence: 99%
See 2 more Smart Citations